2011
DOI: 10.1007/s11739-011-0518-6
|View full text |Cite
|
Sign up to set email alerts
|

Regional short-term climate variations influence on the number of visits for renal colic in a large urban Emergency Department: results of a 7-year survey

Abstract: The pathogenesis of renal stones is an intricate process and varies widely depending on the composition of stones. There is also a marked geographic variability, strongly attributable to the mean annual temperature (MAT) and, to a lesser extent, on the seasons. Previous investigations report peaks in Emergency Department (ED) visits for renal colic during the summer. The aim of the present investigation is to assess the influence of day-by-day climate changes on the number of visits due to renal colic in our E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 32 publications
0
17
0
3
Order By: Relevance
“…There has been a significant improvement in the medical management of the ureteric calculi with the introduction of effective medical therapeutic agent in the market. 9 Malan et al first demonstrated the presence of alpha adrenergic receptors in the lumen ureter in 1970. Characteristic distribution of alpha one receptor subtypes in distal, middle and proximal segments is alpha 1d, alpha 1a, and alpha 1b.…”
Section: Discussionmentioning
confidence: 99%
“…There has been a significant improvement in the medical management of the ureteric calculi with the introduction of effective medical therapeutic agent in the market. 9 Malan et al first demonstrated the presence of alpha adrenergic receptors in the lumen ureter in 1970. Characteristic distribution of alpha one receptor subtypes in distal, middle and proximal segments is alpha 1d, alpha 1a, and alpha 1b.…”
Section: Discussionmentioning
confidence: 99%
“…This also holds true, for example, in the correlations found between renal colics and climate variations, since the pathogenesis of renal stones is a complex, time-consuming and multifaceted process, but the abrupt onset of the colic just entails a short period, in a specific clinical and environmental condition. 4,5 Due to lack of data, we could not analyze the possible correlations with other climatic variable, such as winds, 58 day-light 59 and time spent outside. 60 We here describe a heterogeneous sample of patients visited for psychiatric emergencies, and it remains unclear whether different diagnostic subgroups may display similar correlations.…”
Section: Articlementioning
confidence: 99%
“…1 From the middle of the past century, however, this phenomenon has been investigated with more appropriate epidemiological and clinical tools, so that we have now reached a point where we can better analyze some popular beliefs under the light of science. Several studies, with different strength of evidence, have shown that an association may exist between meteorological variables and different human disorders such as stroke, 2,3 renal colic, 4,5 myocardial infarction, 6 atrial fibrillation, [7][8][9][10] asthma, 11,12 and arthritic pain. 13 Subjective experiences referred from patients, including variation in pain thresholds and mood swings associated with weather changes, seem to support the existence of a genuine relationship and pave the way to further research on this topic.…”
Section: Introductionmentioning
confidence: 99%
“…This geographic variability has been evaluated to assess whether race, age, education, body mass, or diet affects the frequency data, but ambient temperature and sunlight levels remain the greatest risks [ 68 ]. Following extremely warm and dry temperature swings in the Italy, it has been noted that there is a 1-month window where both the incidence and prevalence of stone disease rise [ 69 ].…”
Section: Modern Urolithiasis Epidemiologymentioning
confidence: 99%